Copper isotope compositions of Cenozoic mafic-intermediate rocks of the Northern Great Basin and Snake River plain (USA) - Maynard, Annastacia Lin (Kansas State University, 2016)
Mid-Miocene epithermal Au-Ag ores of the northern Great Basin USA are related to magmatism associated with the inception of the Yellowstone hotspot. The geochemical chemical connection between these ores and spatially and temporally related volcanism is not well understood, but has been suggested (Kamenov, 2007; Saunders et al., 2015). These Cu- and Pb- isotope studies show that the ore and associated gangue minerals have different sources of Pb, which supports evidence that the metal(loids) originate from a deep magmatic source (Saunders et al., 2008). Cu isotopes as a tool for exploring linkages between ore deposits and related volcanic rocks is a new and evolving field. A suite of mid-Miocene Northern Great Basin (NGB) and Snake River Plain (SRP) volcanic rocks was analyzed by aquaregia leach for their δ⁶⁵Cu compositions. These samples have all been previously characterized and include basalts, trachybasalt, basaltic andesites, and basaltic trachyandesites that are representative of regional flood basalt magmatism and younger basalt eruptions in central Idaho. Included are rocks from the Santa Rosa-Calico volcanic field, NV (e.g., Buckskin-National district); Owyhee Mountains, ID (Silver City District); Midas, NV region, near Jarbidge, NV; and a locality proximal to Steens Mountain, OR. Also included are two Pleistocene basalts from the central Snake River plain unequivocally related to the Yellowstone hotspot volcanism (McKinney Basalt and Basalt of Flat Top Butte), and one Eocene basalt from the Owyhee Mountains that is related to pre-hotspot arc volcanism. International rock standards ranging from ultramafic to intermediate were also analyzed in this study for comparison. Our new δ⁶⁵Cu data greatly expands the range of known Cu isotopic compositions for basalts, with values ranging from -0.84‰ to +2.61‰. These values overlap with the δ⁶⁵Cu of regional ores, further suggesting a link between the source(s) of the ores and the NGB rocks. The range of δ⁶⁵Cu values also overlaps with mantle rock values, suggesting that the Cu isotopic composition may be a signature derived from the mantle source. Fractionation mechanisms that cause such a broad range in Cu isotopes are still unclear but liquid-vapor transitions and mantle metasomatism are being explored. Furthermore, δ⁶⁵Cu values of international rock standards reported in this study did not agree with previously reported data (Archer and Vance, 2004; Bigalke et al., 2010; Moeller et al., 2012; Liu et al., 2014, 2015) suggesting that aquaregia leach may not be a preferable technique when analyzing volcanic rocks.
Keywords: Cooper isotopes; Epithermal deposits; Au-Ag; Northern Great Basin; Isotope fractionation